The Livelihood Strategy for Lowland Rice Farming Families in Namang Village, Central Bangka Regency - Siti Saleha; Iskandar Zulkarnain; Michael Jeffri Sinabutar (Profesional Muda Cendekia Publishing, 2022)
The family livelihood strategy of lowland rice farmers in Namang Village is an effort of lowland rice farmers to overcome poverty, dependence, and injustice that occurs due to the narrowness of paddy fields, low education, and low social status. This study aims to analyze the livelihood strategies of rice farming families in Namang Village in order to stabilize the family economy. This research was conducted in a descriptive qualitative way with data collection methods, namely through interviews, observations, and documentation. This study shows that there are three livelihood strategies for lowland rice farming families. Based on the theory from Scoones (2009), the family livelihood strategies of lowland rice farmers in Namang Village are, 1. Agricultural intensification 2. Multiple livelihood patterns 3. Spatial engineering. Lowland rice farming families in Namang Village carry out agricultural intensification through the development of agricultural crops such as vegetables, and the development of traditional to modern technology. Then a double income pattern by utilizing all family members to earn a living. Lastly, spatial engineering by migrating out of the area.